Self-Efficacy About Sexual Behavior Among Islamic Boarding School Students - Prabamurti, Priyadi Nugraha; Suryoputro, Antono; Shaluhiyah, Zahroh; Margawati, Ani; Kusumawati, Aditya; Indraswari, Ratih; Handayani, Novia; Husodo, Besar Tirto (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
Having premarital sexual intercourse has a broad risk impact on health. This is in accordance with the teachings of Islam that should be upheld by all Muslims, with no exception for students living in Islamic boarding schools. To Islamic values and culture, students should have strong self-efficacy to prevent them from engaging in sexual behavior. This study aims to determine the effect of self-efficacy on the sexual behavior of students living in Islamic boarding schools. This cross-sectional study sampled 150 students who lived in Islamic boarding school in Semarang, Indonesia. Students at Islamic boarding schools who had premarital sex were more likely to be found in adolescents aged 19 years (15.2%), male (9.5%), had low self-efficacy (18.2%), and ever accessed pornography (23.1%). Accessing pornography was influenced by sex (p = 0.021, OR = 0.235), while premarital sexual intercourse behavior was influenced by age (p = 0.013, OR = 10.716) and self-efficacy (p = 0.043, OR = 4.602). Younger students with low self-efficacy are more likely to practice premarital sexual intercourse. This study found that accessing pornography had no effect on the practice of sex carried out by students in Islamic boarding schools. The health ministry needs to work with the religious affairs ministry to design programs aimed at increasing self-efficacy among students in Islamic boarding schools.